(untitled) (Jurnal Teknologi (Sciences & Engineering), 2025)
The COVID-19 pandemic has led to an increase in worldwide consumption of nitrile butadiene rubber (NBR) gloves and disposable face masks (DFM), resulting in environmental contamination. Thus, this research was conducted to compare the physical properties of modified bitumen penetration grade 60/70 and to evaluate the performance of modified Stone Mastic Asphalt (SMA-14) mixtures when using both materials as fibers. NBR gloves and DFM were collected around the campus of Universiti Teknologi MARA (UiTM) Permatang Pauh and were later sanitized and cut into strips of 6 mm maximum length. By applying the softening point and penetration tests, the physical parameters of modified bitumen PEN 60/70 were compared to those of bitumen with NBR and DFM as additives. The Unconfined Compression Strength (UCS) and binder drain-down tests were also conducted to compare the performance and binder-draining properties of modified SMA-14 mixtures using both dry and wet process methods when both fibers were added. The results showed that adding 3%, 6%, and 9% of NBR to modified bitumen PEN 60/70 increases the softening value and penetration depth, while DFM decreases both test values for all percentages. Besides, 3% NBR and 6% DFM strengthen the mixtures, making the bitumen less likely to drain in both dry and wet processing. All test results were compared against the Public Works Department’s requirements and passed the set standard. It is concluded that adding 3% NBR and 6% DFM as pavement additives positively impacts its performance and increases the service life.